METHODOLOGY OF RESEARCH INTO THE EARTH'S CRUST STRUCTURE VIA REMOTE SENSING TECHNOLOGIES - Azimov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Five fundamentals to investigate Earth's crust structure using remote aerospace technologies are given conceptual and phenomenological consideration. The first principle refers to the paragenesis of the oppositely directed physical forces. These are, namely, the force of attraction, and the force of repulsion. The second principle underlies the two groups of the geological driving forces (internal and external ones) that determine the appearance and the evolution of the lithospheric structure. The third principle of applying remote sensing application for geological purposes is based on two types of deformations: plastic (quasiplastic) rock deformation and brittle (quasibrittle) deformation. The fourth principle underpins dynamics of both permanent and interrupted energy-mass-exchange in the natural Earth's geosystems, which is a property of matter and its forms of motion. The fifth principle states that specific modern landscapes and their anomalies (being geoindicators of interior structure of the geological substrate and energy-mass exchange) are differentiated by the spectral features of the reflected, absorbed, and emitted electromagnetic radiation in variable wave ranges. As a result, they are distinguished by these characteristics and may be imaged and identified via remote sensing data.
Keywords: methodology; the Earth's crust; geological dynamics; remote sensing of the Earth; landscape geoindicators